Investigation of Soil-Structure Interaction for Design of Reinforced Concrete Structures under Earthquake Load - Saffet Kılıçer; Korhan Özgan (Doğal Afetler ve Çevre Dergisi)
One of the most common natural disasters in our country is earthquakes with strong ground motion. Earthquake damages structures with the impact of ground shaking. Prediction of earthquake magnitude in advance is a great importance in the civil engineering discipline to minimize possible damages during the earthquake. Therefore, understanding of structural behavior correctly is as important as the estimation of the possible earthquake magnitude. For this reason, structures should be modeled accurately and realistically. Reinforced concrete structures are usually designed using commercial software defined either as rigid or with elastic springs at the base. In this study, considering the earthquake recording of 1999 Kocaeli, a 12-storey reinforced concrete structure was analyzed with rigid foundation assumption, Winkler and Modified Vlasov models. An interface was coded in MATLAB to exchange data between SAP2000 and MATLAB. Thanks to the interface, SAP2000 has gained the ability of performing analyses with modified Vlasov model. In this way, periods, base shear forces, column axial forces, column bending moments and lateral displacements of the structures were compared for each subsoil model. At the end of the study, it is observed that the effect of subsoil on the structural behavior is an indispensable design factor for the reinforced concrete structures.